2014
DOI: 10.1088/0004-6256/148/6/128
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Analysis of Solar Activity and Its Link With the Arctic Oscillation Phenomenon

Abstract: Based on spectrum analysis, we provide the arithmetic expressions of the quasi 11 yr cycle, 110 yr century cycle of relative sunspot numbers, and quasi 22 yr cycle of solar magnetic field polarity. Based on a comparative analysis of the monthly average geopotential height, geopotential height anomaly, and temperature anomaly of the northern hemisphere at locations with an air pressure of 500 hPa during the positive and negative phases of AO (Arctic Oscillation), one can see that the abnormal warming period in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The main contribution of this work is that the periodic phenomena revealed by the sunspot data are limited within the time period of the 11-year cycle as well as the periodicities of the orbits of the planets, showing the possible effect of the orbits of the planets on the Sun's plasma. This contribution fills a gap that exists in the research in relation to the appearance of planetary periodicities in sunspot time series, since, to date, dominant studies have dealt with much longer periodicities (e.g., millennia or centuries) and were based on the way the solar magnetic field in the heliosphere modulates cosmic rays, influencing the production rate of radionuclides on Earth [4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main contribution of this work is that the periodic phenomena revealed by the sunspot data are limited within the time period of the 11-year cycle as well as the periodicities of the orbits of the planets, showing the possible effect of the orbits of the planets on the Sun's plasma. This contribution fills a gap that exists in the research in relation to the appearance of planetary periodicities in sunspot time series, since, to date, dominant studies have dealt with much longer periodicities (e.g., millennia or centuries) and were based on the way the solar magnetic field in the heliosphere modulates cosmic rays, influencing the production rate of radionuclides on Earth [4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Jacob Oloketuyi et al [5] conducted an analysis of daily data from January 1995 to December 2018, exploring the periodic behavior and the relationship between sunspot numbers, cosmic ray intensity, and solar wind speed. Weizheng Qu et al [6] presented arithmetic expressions for the quasi-11-year cycle, 110-year century cycle of relative sunspot numbers, and quasi-22-year cycle of solar magnetic field polarity through a spectrum analysis. Furthermore, M. G. Ogurtsov et al [7] confirmed the distinguishability of two long-term variations in solar activity, namely the Gleissberg and Suess cycles, at least over the last millennium.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the polar regions are particularly sensitive to solar eruptions. That is to say, the extra solar energy input outside the Earth-air system is an important factor that stimulates the large-scale, long-period variations of the Arctic Oscillation [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the polar regions are particularly sensitive to solar eruptions. That is to say, the extra solar energy input outside the Earth-air system is an important factor that stimulates the large-scale, long-period variations of the Arctic oscillation 4 6 .…”
Section: Introductionmentioning
confidence: 99%